Bifid triple viable preparation combined with enteral nutrition as a supportive treatment for acute ischemic stroke: a systematic review and meta-analysis - Kong, Yumeng; Yu, Yunfeng; Deng, Juan; Yu, Rong; Liu, Xiu (Frontiers in Microbiology, 2024)
Background: The benefits and risks of bifid triple viable preparations in patients with acute ischemic stroke (AIS) are still controversial. This study aimed to assess the efficacy and safety of bifid triple viable preparations in combination with enteral nutrition for the management of AIS. Methods: Eight public databases including China National Knowledge Infrastructure, China Biology Medicine, VIP, WanFang, EBSCO, PubMed, Cochrane Library, and Web of Science were searched for relevant clinical literature, published through January 2024. These data were then used in the present meta-analysis. Results: A total of 15 studies involving 1,544 patients were included in the meta-analysis. In terms of nutritional status, the results showed that compared with enteral nutrition alone, the bifid triple viable preparation combination group increased the levels of total protein (mean difference [MD], 5.53; 95%confidence interval [CI], 1.94–9.12; P=0.003), albumin (MD, 4.01; 95%CI, 2.96–5.06; P<0.00001), prealbumin (MD, 23.08; 95%CI, 16.22–29.95; P<0.00001), hemoglobin (MD, 9.31; 95%CI, 6.34–11.27; P<0.00001), and transferrin (MD, 0.64; 95%CI, 0.23–1.05; P = 0.002); in terms of neurological function, it improved the Glasgow Coma Scale (MD, 2.09; 95%CI, 0.69–3.49; P=0.03), National Institute of Health Stroke Scale (MD, -3.07; 95%CI, -3.73 to -2.40; P<0.00001), and Neurological Disability Score (MD, -6.68; 95%CI. -7.29 to -6.08; P<0.00001); in terms of intestinal barrier function, it reduced the levels of endotoxin (MD, -0.55; 95%CI, -0.71 to -0.39; P<0.00001), D-lactic acid (MD, -3.17; 95%CI, -4.07 to -2.26; P<0.00001), diamine oxidase (MD, -4.39; 95%CI, -6.20 to -2.57; P<0.00001), and endothelin (MD, -21.35; 95%CI, -27.86 to -14.83; P<0.00001); in terms of immune function, it increased the levels of immunoglobulin G (MD, 1.01; 95%CI, 0.20–1.82; P=0.01) and immunoglobulin M (MD, 0.16; 95%CI, 0.02–0.30; P=0.03). Additionally, it reduced the incidence of pulmonary infection, vomiting, constipation, and diarrhea, while there were no significant differences in total adverse events, abdominal distension, anorexia, reflux, gastrointestinal bleeding, or electrolyte disturbance. Conclusion: The addition of bifid triple viable preparation to enteral nutrition improved the nutritional status, neurological function, intestinal barrier function, and immune function of patients with AIS, and reduced the risk of infection and gastrointestinal events.